Histologic Evaluation of the Osteoinductive Property of Autogenous Demineralized Dentin Matrix on Surgical Bone Defects in Rabbit Skulls Using Human Amniotic Membrane for Guided Bone Regeneration - Gomes, Mônica Fernandes [UNESP]; Da Silva Dos Anjos, Mário James; De Oliveira Nogueira, Terezinha [UNESP]; Catanzaro Guimarães, Sérgio Augusto (My University, 2001)
The aim of this investigation was to evaluate the osteoinductive property of autogenous demineralized dentin matrix (ADDM) on experimental surgical bone defects in the parietal bone of rabbits using the guided bone regeneration (GBR) technique incorporating human amniotic membrane (HAM). Thirty-six rabbits were divided into 2 groups, HAM and ADDM+HAM. It was possible to conclude that HAM did not interfere with bone repair and was resorbed. Slices of ADDM induced direct bone formation and were incorporated by the newly formed bone tissue and remodeled. The bone defects healed faster in the ADDM+HAM group than in the group with HAM only.
Keywords: Autogenous demineralized dentin matrix; Biologic dressings; Bone repair; Guided tissue regeneration; Human amniotic membrane; biomedical and dental materials; coloring agent; Demineralized Dentin Matrix; diagnostic agent; amnion; animal; artificial membrane; autotransplantation; biodegradable implant; bone development; bone disease; bone prosthesis; bone regeneration; bone remodeling; dentin; follow up; human; pathology; physiology; rabbit; skull; wound healing; Absorbable Implants; Amnion; Animals; Bone Diseases; Bone Regeneration; Bone Remodeling; Bone Substitutes; Coloring Agents; Dental Materials; Dentin; Follow-Up Studies; Humans; Membranes, Artificial; Osteogenesis; Parietal Bone; Rabbits; Transplantation, Autologous; Wound Healing